The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/pcp/pcu058
|View full text |Cite
|
Sign up to set email alerts
|

miR396a-Mediated Basic Helix–Loop–Helix Transcription Factor bHLH74 Repression Acts as a Regulator for Root Growth in Arabidopsis Seedlings

Abstract: miR396 targets seven GROWTH-REGULATING FACTOR (GRF) genes and the BASIC HELIX-LOOP-HELIX (bHLH) TRANSCRIPTION FACTOR 74 gene (bHLH74) in Arabidopsis. Previous research revealed that the miR396 target module regulates cell proliferation and plays a critical role in leaf development. However, no additional biological functions of miR396 have been investigated in detail. In this study, T-DNA insertion mutants and transgenic plants with altered levels of miR396 or its target genes were used to characterize the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 37 publications
1
83
1
Order By: Relevance
“…However, our data show that the repression of PLT genes by the GRFs contributes to the quantitative regulation of PLT levels in the root meristem, as a reduction in the GRFs by miR396 or an increase in their levels by the use of rGRF transgenes or miR396 target mimics results in opposite changes of PLT expression levels. It is interesting that, in the most extreme cases, miR396 overexpression produces defects in cell elongation, which were also observed previously (Bao et al, 2014). Cell elongation is also inhibited by high local levels of PLT (Mähönen et al, 2014).…”
Section: Grfs Repress Stem Cell-like Properties In Tacssupporting
confidence: 79%
See 1 more Smart Citation
“…However, our data show that the repression of PLT genes by the GRFs contributes to the quantitative regulation of PLT levels in the root meristem, as a reduction in the GRFs by miR396 or an increase in their levels by the use of rGRF transgenes or miR396 target mimics results in opposite changes of PLT expression levels. It is interesting that, in the most extreme cases, miR396 overexpression produces defects in cell elongation, which were also observed previously (Bao et al, 2014). Cell elongation is also inhibited by high local levels of PLT (Mähönen et al, 2014).…”
Section: Grfs Repress Stem Cell-like Properties In Tacssupporting
confidence: 79%
“…The miR396-GRF interaction is conserved among angiosperms and gymnosperms (Jones-Rhoades and Bartel, 2004;Debernardi et al, 2012). It has been shown that overexpression of miR396 represses organ growth in Arabidopsis (Liu et al, 2009;Rodriguez et al, 2010;Bao et al, 2014;Liang et al, 2014b), whereas increased levels of the GRFs promote growth, especially in leaves (Kim et al, 2003;Horiguchi et al, 2005;Rodriguez et al, 2010), yet the mechanisms underlying the functions of the GRFs are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although initial reports identified GRFs as transcription factors with a function in leaf and stem development, recent studies have uncovered functions of GRFs in other developmental processes such as flowering, seed and root development and regulation of plant longevity26274753545556. Also, different stresses lead to changes in miR396 accumulation, including interactions with nematodes, bacteria, oomycetes and abiotic stress, among others2844575859.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some miRNA-mRNA pair interactions were observed in radish taproot thickening process. In detail, the ARFs (targeted by miR160 and miR167), IAA11 (targeted by miR5021) and bHLH74 (targeted by miR396) were found to be involved in root growth and regulated vascular cell differentiation (Bustos Sanmamed et al, 2013; Bao et al, 2014; Zhang et al, 2014b). The LRR protein kinase-like protein gene ( LRR , targeted by miR1510 and miR6474), LACs (targeted by miR397) and EXPA9 (targeted by miR8005 and miR3447) were involved in cell wall formation and loosening (Dolan and Davies, 2004; Cai et al, 2006), while the CESA6 (targeted by miR5021) and BAM4 (targeted by miR5293) genes were involved in cell wall synthesis and degradation (Cosgrove, 2005; Van Sandt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%